Numerical Analysis of Soft Soil Improvement using Pile at Airport Construction Project - Himatul Farichah; Dio Alif Hutama; Dian Purnamawati Solin (JACEE (Journal of Advanced Civil and Environmental Engineering), 2023)
Construction on the soft ground poses an excellent challenge for geotechnical engineers. Several engineering problems such as bearing capacity failure and differential settlement could occur either during or after the construction phase due to high compressibility and low shear strength. Nowadays, a number of soil improvement techniques are available to solve such problems. However, each method has its advantages and disadvantages. In this study, soil improvement analysis using pile were performed with three variations depths so called 12 m, 18 m, and 24 m from the ground level. A finite element simulation has been performed using PLAXIS 2D. The pile has been modeled as plate and Mohr-Coulomb model was used for soil model. The results show that the deeper the pile, the settlement will be decreasing. Moreover, the axial force and bending moment of the pile obtained from the output of PLAXIS 2D were also presented to assess the performance of the soil improvement technique.